A comprehensive approach for bridge performance evaluation under rockfall impact integrated with geological hazard analysis. (November 2022) - Zhang, Jingfeng; Wang, Rui; Han, Wanshui; Bao, Han
Highlights: The bridge safety under rockfall impact was evaluated by integrating with the geological hazard analysis; The probability distributions of key impact parameters were obtained based on Monte Carlo simulation; The characteristic values were utilized as impact parameters to perform structural dynamic analysis; The impact translational velocity kept constant under certain geological conditions; The post-impact performance of bridge sub- and superstructure was quantified by residual capacity and stiffness. Abstract: Rockfall is one kind of major hazard that seriously threatens the safety of bridge structures passing through mountainous areas. The complexity of geological conditions in mountainous areas makes it difficult to determine the initial impact parameters of falling rock in the bridge performance analysis. At present, the subjective and deterministic methods are adopted to get the initial motion parameters of the falling rock for evaluating the structural responses. In this paper, the probability distributions of falling rocks collision parameters are obtained by the rockfall Monte Carlo simulations. Then the characteristic values from the probability distribution of rock motion parameters are taken as the input parameters in the dynamic simulation of bridge structure. Finally, three-dimensional nonlinear dynamic analysis is employed to evaluate the safety of the bridge structure under rockfall hazards. The residual resistance index (RRI) is presented for quantifying the post-impact performance of bridge pier and girder under rock collision. The structural safety is mainly dominated by the impact mass and translational velocity of the falling rock rather than the rotational velocity and impact angle. The rock shape also has non-negligible influence on the structural dynamic responses and performance, and the cube-like rock induces more severe structural damage than other shapes. According to the RRI and probability distribution of rock mass, the non-exceedance probability of RRI is obtained which can be used for the risk analysis of rockfall impacting on bridges. The proposed comprehensive approach for bridge performance evaluation considers the uncertainty of rockfall characteristics, and it provides more reasonable solution to investigate the impact performance of bridge structure under rockfall disasters.